2013
DOI: 10.1002/anie.201303881
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nitrate Binding in Competitive Hydrogen Bonding Solvents: Do Anion–π Interactions Facilitate Nitrate Selectivity?

Abstract: New tripodal urea receptors demonstrate preferential binding of anions over competitive hydrogen bonding solvents. 1H NMR titrations in 10% DMSO-d6/CDCl3 show a higher affinity for nitrate over the halides for the fluorinated receptor, which is lost when the fluorines are removed. An “anion–π” interaction between the nitrate and the π-system of the ethynyl-substituted arene is proposed as the source of this selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…However, crystal and solution studies have also demonstrated the existence of alternative W and S conformations in this general class of bisurea arylethynyl receptors. 2931 …”
Section: Resultsmentioning
confidence: 99%
“…However, crystal and solution studies have also demonstrated the existence of alternative W and S conformations in this general class of bisurea arylethynyl receptors. 2931 …”
Section: Resultsmentioning
confidence: 99%
“…[78] The desired selectivity of 29 for NO 3 − over halides was supported by 1 H NMR titrations in 10% DMSO/CDCl 3 . The X-ray crystal structure favors an uncommon explanation for selectivity, namely an anion–π type interaction between NO 3 − and the alkyne attached to the central arene, where the anion rests offset from the center of a tripodal binding pocket (Figure 17 colored inset).…”
Section: Charged Speciesmentioning
confidence: 99%
“…We have previously reported on a family of modular arylethynyl receptors for anion binding and fluorescent sensing using 2,6-bis(2-anilinoethynyl)pyridine (18-25), -bipyridine (24, 26-28), -phenanthroline (28), -benzene (29-30), and -thiophene (24) scaffolds. The anilines are further functionalized with amide (20), sulfonamide (18, 24), or urea (19, 21-23, 25-30) groups to provide capabilities such as anion selectivity for nitrate (30) and H 2 PO 4 − (26), water solubility (25) or metal coordination (27). An example of a pyridine receptor with sulfonamide arms (e.g., 1 ) is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%